Rigorous spectral analysis of the metal-insulator transition in a limit-periodic potential - Schulz-Baldes, Hermann; Zarrouati, Marc (Journal of Statistical Physics, 1998)
We consider the limit-periodic Jacobi matrices associated with the real Julia sets of fλ(z) = z2-λ. for which λε[2, ∝) can be seen as the strength of the limit-periodic coefficients. The typical local spectral exponent of their spectral measures is shown to be a harmonic function in λ decreasing logarithmically from 1 to 0.
UnivIS-Import:2015-03-05:Pub.1998.nat.dma.pma22.rigoro
Keywords: Julia matrices; Local spectral exponents